2008
DOI: 10.1124/dmd.108.024984
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Pharmacokinetics in Pregnancy

Abstract: ABSTRACT:The objective of this study was to determine the pharmacokinetic parameters of clonidine during pregnancy compared with previously published data in nonpregnant subjects. Serial blood and urine samples were collected in 17 women during mid to late pregnancy over one steady-state dosing interval to determine clonidine noncompartmental pharmacokinetic parameters (n ‫؍‬ 17) and creatinine clearance. In six of these pregnant subjects, maternal and umbilical cord (venous and arterial) plasma samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 15 publications
(24 reference statements)
9
47
0
1
Order By: Relevance
“…However, clinical observations indicate that higher doses or more frequent dosing of clonidine may be required during pregnancy (Buchanan et al, 2009). Consistent with those observations, we have recently found that apparent oral clearance of clonidine in pregnant women is 80% higher compared with that reported in the literature for men and nonpregnant women (Buchanan et al, 2009).…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…However, clinical observations indicate that higher doses or more frequent dosing of clonidine may be required during pregnancy (Buchanan et al, 2009). Consistent with those observations, we have recently found that apparent oral clearance of clonidine in pregnant women is 80% higher compared with that reported in the literature for men and nonpregnant women (Buchanan et al, 2009).…”
Section: Introductionsupporting
confidence: 76%
“…Consistent with those observations, we have recently found that apparent oral clearance of clonidine in pregnant women is 80% higher compared with that reported in the literature for men and nonpregnant women (Buchanan et al, 2009). The renal component of clonidine clearance remained unchanged as we described previously (Buchanan et al, 2009), suggesting that alteration in bioavailability and/or nonrenal clearance is responsible for the observed change in clonidine pharmacokinetics during pregnancy. Limited studies have suggested that oral drug absorption is not altered in pregnancy (Anderson, 2005), which leaves modulation of nonrenal clearance as a more likely explanation for the change in oral clonidine clearance in pregnancy.…”
supporting
confidence: 77%
See 3 more Smart Citations